Effect of Inner Catalyst Layer with PTFE Binder on Performance of High Temperature Polymer Electrolyte Membrane Fuel Cells. (3rd July 2019) - Lee, Eunae; Kim, Do-Hyung; Pak, Chanho
Abstract : Herein, gas diffusion electrodes (GDEs) structured with a double catalyst layer were fabricated by introducing an inner catalyst layer containing PTFE. The Pt loading of the inner catalyst layer with Polytetrafluoroethylene (PTFE) was varied over 0.1–0.9 mg·cm -2 . The fabricated GDEs were applied to the membrane electrolyte assembly (MEA) as a cathode to evaluate the single cell performance of high temperature polymer electrolyte membrane fuel cells (HT-PEMFCs). Peak power density improved by 33%, from 266 mW·cm -2 to 355 mW·cm -2 for 0.1 mg·cm -2 of Pt loading of the inner catalyst layer. This substantial enhancement in single cell performance even with a small amount of Pt loading of the inner catalyst layer results from highly hydrophobic catalyst layers leading to improved mass transport. As the Pt loading of the inner catalyst layer increases, the MEA performance in fuel cells improved; however, the performance saturated at Pt loading of 0.5 mg·cm -2 and above.